Kerkelijke betrokkenheid in de 21ste eeuw - Kregting, Joris; Sederel, Charlotte (Religie & Samenleving, 2013)
Due to modernization, individualization and de-institutionalization, there has been a long period of decline in church membership rates in the Netherlands. In this article based on both survey research and church administrations, several levels of involvement are explored within church membership. Nowadays, 40% of the Dutch population is an initiated member of a Christian church. Almost 30% of the Dutch population considers themselves as a member of a church and almost 10% attends church on a regular basis. The participating church members have, besides their religious socialization, social and intrinsic motives to belong to their church. For all other members, church involvement seems to be an inheritance of their parents and almost nothing more than that. This has strong implications for the future while we expect that these large groups of non-participating members will not pass their church involvement on to next generations. Therefore church membership rates on all levels of involvement are expected to drop further.